‘Cosa ho voluto fare scrivendo poesie?’ Autodeterminazione e assillo metrico in Amelia Rosselli - Miliucci, Fabrizio (Incontri. Rivista europea di studi italiani, 2015)
‘Cosa ho voluto fare scrivendo poesie?’ Amelia Rosselli’s self-determination and metrical concerns This article analyses a number of Amelia Rosselli’s lesser-known writings in which the poet comments to varying degrees on her own work. These texts offer an insight into the poet’s self-image and its development over the years, particularly through the metrical concerns central to her work from the publication of her first book Variazioni belliche (1964). A number of different themes arise. The question from which the essay takes its title (‘What did I want to do by writing poems?’) reveals a pressing attitude towards the public, the limits of which are nevertheless vaguely defined, as well as a general fear of being misinterpreted at the moment of publication. The poet is driven by this concern to make her poetry more accessible without compromising the source of her inspiration, in spite of the tension between these two factors. Her self-commentary assumes an ambiguous status: not entirely separated from the creative process, in some cases it can be considered the continuation of artistic conception. Creation and knowledge seem to switch roles in some typically Rossellian pieces, which display strong artistic value in spite of their openly essay-like nature (see Spazi metrici or La serie degli armonici). This study also considers secondary material (the two Curricula, written for journalistic reasons, and interviews) which provide images of the poet, her attitude towards publication and the vaguely defined limits of a production suspended between shock and a willingness to communicate.